Genotyping and DNA Sequencing of Toxoplasma gondii from Women and Domestic Chickens in the Wasit Province Iraq - May Naji Al-khanak; Suroor S. Salman (Indian Journal of Forensic Medicine & Toxicology, 2021)
The current study included two main axes, which are the investigation of the rates of toxoplasmosis in theplacenta in pregnant women who experience miscarriage and normal delivery, and the rate of infection inthe tissues of domestic chicken (brain, liver and muscles) in Wasit province. A total of 96 samples werecollected and subjected to PCR. The sample included 24 tissue samples collected from women of normalchildbirth or abortion, and 72 samples collected from local chickens, 24 for each of (brain, liver and muscles).Results revealed that the difference between the infection rate in women (62.5%) and the infection rate inthe chickens (56.9%) was not significant. Also, the infection rates of Brain (62.5%), Liver (70.8%), andMuscles(58.3%) of chicken were not significant.